Geotechnical properties of Brazilian weak sedimentary rocks - De Oliveira Campos, Jayme [UNESP]; Paraguassu, Antenor Braga; Frazão, Ely Borges; Soares, Lindolfo (My University, 2014)
The sedimentary rocks cover about 70% of the Brazilian territory. Large sedimentary basins, from the Paleozoic to the early Cenozoic, present a wide variability of lithology, raging from coarse grained rocks as the conglomerates, to the fine grained siltstones and claystones. Geotechnical parameters (index properties, resistance to uniaxial and triaxial compression strength, deformability, disaggregation, slaking, drillability, erosion resistance, etc.) have been determined for the several rocks types, concerning various projects like roads, channels, dams, tunnels, etc. The tropical weathering has been considered a factor of great importance in the evolution of these rocks, due to the decrease of their resistance and deformability in some cases, and the lateritization and cementation, in others. This paper briefs information regarding the geotechnical properties of several sedimentary rocks in Brazil, as well as gives some guidelines to foresee their characterization related to strength, weathering and slaking. In order to be restricted to the subject itself, we will not observed the metamorphic rocks of low degree and the sedimentary rocks strengthened by silicification, such as the sandstones silicified by the basaltic flows.
Keywords: Brazilian sedimentary basins; Rock mechanics; Soft rocks